Analysis of inventory system with three stages of deterioration (Global Journal of Science Frontier Research, 2012)
In this article, we consider a continuous review perishable inventory system with instantaneous replenishment policy. The status of perishable item in inventory is assumed to be in any one of the three stages good, average and damaged. The demand process is assumed to be Poisson, replenishment is instantaneous and the deterioration process is prescribed by certain transition probability matrix. Various stationary system performance measures are obtained. The total system maintenance cost rate is calculated and an optimal value of the S is obtained.. The results are illustrated numerically.
Keywords: Inventory control system; Perishable inventory; Poisson demand Continuous time Markov chain; Optimization